2010
DOI: 10.4149/neo_2010_05_422
|View full text |Cite
|
Sign up to set email alerts
|

The effect of probiotic microorganisms and bioactive compounds on chemically induced carcinogenesis in rats

Abstract: Diet interventions and natural bioactive supplements have now been extensively studied to reduce risks of colon cancer, which is one of the major public health problem throughout the world. The objective of our investigation was to study the effects of probiotic, prebiotic, nutritional plant extract, and plant oil on selected biochemical and immunological parameters in rats with colon cancer induced by N,N dimethylhydrazine (DMH). Male and female Wistar albino rats were were fed by a high-fat (HF) diet (10% fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 32 publications
2
22
0
1
Order By: Relevance
“…18 Lactobacilli are capable of competitively inhibiting carcinogen and mutagen formation, altering overall metabolism, adsorbing and removing toxic and mutagenic metabolites and producing protective metabolites. 19 In the context of colorectal cancer, the prevention mechanism exerted by probiotics may be a combination of different actions such as intestinal microbiota modification, [20][21][22][23][24][25][26] inactivation of cancerogenic…”
Section: Experimental Evidence Adhesion To the Gastrointestinal Mucosamentioning
confidence: 99%
“…18 Lactobacilli are capable of competitively inhibiting carcinogen and mutagen formation, altering overall metabolism, adsorbing and removing toxic and mutagenic metabolites and producing protective metabolites. 19 In the context of colorectal cancer, the prevention mechanism exerted by probiotics may be a combination of different actions such as intestinal microbiota modification, [20][21][22][23][24][25][26] inactivation of cancerogenic…”
Section: Experimental Evidence Adhesion To the Gastrointestinal Mucosamentioning
confidence: 99%
“…The results of a previous study indicate that probiotic microorganisms could exert a preventive effect on chemically induced colon carcinogenesis in rats. The application of Lactobacillus plantarum in combination with bioactive compounds was more effective in comparison to the administration of probiotic alone (Bertková et al 2010).…”
Section: Probioticsmentioning
confidence: 99%
“…Based on an experimental study, Bertková et al (2010) suggested that Hippocastani extractum siccum may be a useful candidate agent for colon cancer chemoprevention and treatment. They investigated the effect of probiotic microorganisms and selected bioactive compounds in different combinations on decreasing the concentration of Table 2.…”
Section: Discussionmentioning
confidence: 99%